2000
DOI: 10.1046/j.1365-2958.2000.02076.x
|View full text |Cite
|
Sign up to set email alerts
|

ResD signal transduction regulator of aerobic respiration in Bacillus subtilis: ctaA promoter regulation

Abstract: SummaryA two-component signal transduction system composed of a sensor kinase, ResE, and a response regulator, ResD, encoded by resD and resE genes of the res operon (resABCDE), has a regulatory role in both aerobic and anaerobic respiration. In terms of aerobic respiration, resD functions upstream of ctaA, a gene required for haem A biogenesis and hence for the synthesis of haem A-containing cytochrome terminal oxidases. Although ResD is probably a transcription factor, there was no direct evidence that ResD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 40 publications
3
64
0
Order By: Relevance
“…We have found that strains bearing the cmp mutation bypass the requirement for ResD for full alkaline phosphatase induction (Table 3). However, the cmp mutation does not compensate for the loss of resDE for anaerobic growth (19)(20)(21) or ctaA expression (23,38). Both ctaA and genes required for anaerobic growth require ResD as a transcription activator, suggesting that the nature of the cmp mutation is not to simply fill the role of ResD as a transcriptional regulator for Res regulon members.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that strains bearing the cmp mutation bypass the requirement for ResD for full alkaline phosphatase induction (Table 3). However, the cmp mutation does not compensate for the loss of resDE for anaerobic growth (19)(20)(21) or ctaA expression (23,38). Both ctaA and genes required for anaerobic growth require ResD as a transcription activator, suggesting that the nature of the cmp mutation is not to simply fill the role of ResD as a transcriptional regulator for Res regulon members.…”
Section: Resultsmentioning
confidence: 99%
“…ResD regulates the expression of fnr (21), hmp (21), nasDEF (21), hemN (12), hemZ (12), and the sbo-alb operon (20) under anaerobic conditions and has a role in the regulation of ctaA (23,38), ctaBCDEF (17), resABCDE (31), and petCBD (31) under aerobic conditions. Because ResDE is essential for expression of both ctaA and ctaB, which is required for heme A biosynthesis, ⌬resDE strains lack cytochromes aa 3 and caa 3 .…”
mentioning
confidence: 99%
“…ResE is a membrane-associated sensor kinase that transfers a phosphate to the response regulator ResD. ResD activates the transcription of anaerobically induced genes such as fnr, hmp, and nasD (160,240). During aerobic growth, the transcription of ResDEregulated genes is induced in the postexponential and stationary phases of growth; however, transcription is induced to a greater extent during oxygen-limited growth.…”
Section: Srrabmentioning
confidence: 99%
“…Characterization of ResDE TCS regulon genes has shown that ResD plays an indirect role in Pho regulon induction via heme A synthesis required for terminal oxidases (aa 3 and caa 3 ) (27,42) that oxidize reduced quinones. Reduced quinones were shown to inhibit autophosphorylation of the PhoR in vitro, suggesting that it was the ResD role in terminal oxidase production that positively modulates the PhoR signal (35) upstream of PhoPR.…”
mentioning
confidence: 99%